BERKENALAN DENGAN TASAWUF AL-GAZALI - Abdul Mun'im Amaly; Asep Rifqi Fuad (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2022)
The teachings of Sufism are contradictory teachings until now because many say that it is the teachings of Sufism that push us towards jumud. This paper aims to describe the actual teachings of Sufism in the view of Imam Gazali. This study uses a konsep analisis method by reviewing and analyzing the sources of books, turats, and scientific journals on Sufism, which the researchers then provide an interpretation of the data that has been. This study concludes that there are three core teachings of Islam, namely Islam, Iman, and Ihsan. From